Sodium-ion battery phosphate positive electrode material, preparation method thereof and sodium-ion battery

By coating sulfur-doped graphene and nitrogen and phosphorus co-doped carbon materials on the phosphate core surface of the sodium vanadium phosphate positive electrode material, a mesoporous structure is formed, which solves the problem of low electronic conductivity of existing materials and significantly improves the electrochemical performance.

CN119725425APending Publication Date: 2025-03-28LANGFANG GREEN IND TECH CENT +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311718745.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-09-28
Filing Date
2023-12-14
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The electrochemical performance of vanadium sodium phosphate positive electrode materials in existing sodium ion batteries needs to be improved due to their low electronic conductivity.

Method used

By sequentially coating sulfur-doped graphene and nitrogen and phosphorus co-doped carbon materials on the phosphate core surface, a sodium ion battery phosphate positive electrode material with a mesoporous structure is formed.

Benefits of technology

It significantly improves the conductivity of the positive electrode material, inhibits the dissolution of the active substance, prevents structure collapse, and thus improves the rate performance and cycle stability.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a sodium ion battery positive electrode material and a preparation method and application thereof, and particularly relates to a coated sodium vanadium phosphate positive electrode material and a preparation method and application thereof, and the coated sodium vanadium phosphate positive electrode material is prepared by adopting two different carbon sources through two-step in-situ coating. And meanwhile, the doped oxygen-containing compound is used for carrying out ion doping on the sodium vanadium phosphate positive electrode material, and the electrochemical performance of the sodium vanadium phosphate positive electrode material is further improved by utilizing the synergistic effect formed between the coating layer and the dopant. The obtained coated sodium vanadium phosphate positive electrode material has a mesoporous structure, the reversible specific capacity can reach 111.4 mAh g <-1 > after 100 cycles under the current density of 0.1 A g <-1 >, and the coated sodium vanadium phosphate positive electrode material has excellent rate capability and cycling stability and is suitable for large-scale popularization and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation of positive electrode materials for sodium ion batteries, and in particular relates to a phosphate positive electrode material for sodium ion batteries and a preparation method thereof, and a sodium ion battery. Background Art

[0002] Sodium vanadium phosphate, with the chemical formula Na3V2(PO4)3, belongs to the NASICON class of compounds, and has a theoretical capacity of 117 mAh g -1 , with an operating voltage of about 3.4V, a three-dimensional open skeleton structure, good structural stability and high ionic conductivity, and is widely used as a positive electrode material for sodium ion batteries. However, due to the isolation between VO6, octahedron and PO4 tetrahedron in the NASICON structure, Na3V2(PO4)3 exhibits a weak intrinsic electronic conductivity (1.6×10 -6 S cm -1 ), in order to solve the problem of low electronic conductivity, the main solutions currently adopted by researchers are carbon composite and heteroatom doping.

[0003] CN114300660A discloses a polypyrrole-coated carbon-doped sodium vanadium phosphate positive electrode material and a preparation method thereof. The preparation method comprises: dispersing a vanadium source in water, and then adding a carbon source and stirring evenly; adding a phosphorus source, drying and grinding after reaction, and calcining at high temperature in an inert atmosphere to obtain VPO4 / C; mixing VPO4 / C with Na3PO4 and calcining in an inert atmosphere to obtain carbon-doped sodium vanadium phosphate; mixing carbon-doped sodium vanadium phosphate, a surfactant, a pyrrole monomer and a solvent; and then placing the mixed solution in an ultrasonic device and adding an oxidant solution drop by drop under ultrasonic conditions, and then placing the mixed solution in a water bath for reaction, and drying to obtain the polypyrrole-coated carbon-doped sodium vanadium phosphate positive electrode material.

[0004] CN115472805A discloses a boron-doped carbon-coated modified sodium vanadium fluoride phosphate material and a preparation method thereof, the preparation method comprising: (a) dissolving a vanadium source in deionized water to obtain a first solution; (b) adding a reducing agent to the first solution to react to obtain a second solution; (c) adding a phosphorus source, a sodium source and a fluorine source to the second solution in a stoichiometric ratio, heating and continuously stirring until the solution becomes a gel; drying the gel and grinding it into powder to obtain a sodium vanadium fluoride phosphate precursor; (d) calcining the sodium vanadium fluoride phosphate precursor under inert gas conditions to obtain a sodium vanadium fluoride phosphate material; (e) mixing the sodium vanadium fluoride phosphate material with boric acid in proportion to obtain a first mixture; and (f) calcining the first mixture under inert gas.

[0005] Although the above method improves the electrochemical performance of sodium vanadium phosphate to a certain extent, there is still room for further improvement in its performance. Summary of the invention

[0006] In order to solve the above technical problems, the purpose of the present invention is to provide a sodium ion battery phosphate positive electrode material and a preparation method thereof and a sodium ion battery. The sodium ion battery phosphate positive electrode material of the present invention has excellent electrochemical performance.

[0007] To achieve the above object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a phosphate positive electrode material for a sodium ion battery, wherein the phosphate positive electrode material has a mesoporous structure, and comprises a phosphate core and a first coating layer and a second coating layer sequentially coated from the core to the outside, wherein the first coating layer comprises sulfur-doped graphene, and the second coating layer comprises nitrogen and phosphorus co-doped carbon material.

[0009] The present invention arranges a first coating layer comprising sulfur-doped graphene and a second coating layer comprising nitrogen and phosphorus co-doped carbon material in sequence on the surface of a phosphate inner core, and the sodium ion battery phosphate positive electrode material has a mesoporous structure, which can effectively improve the conductivity, inhibit the dissolution of active substances in the electrolyte, prevent the collapse of the positive electrode material structure, and help improve the rate performance and cycle stability of the positive electrode material.

[0010] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.

[0011] Preferably, based on the total mass of the sodium ion battery phosphate positive electrode material as 100%, the mass fraction of the first coating layer is 0.1-10%, for example, it can be 0.1%, 0.3%, 0.5%, 0.8%, 1%, 3%, 5%, 8% or 10%, as well as specific point values ​​between the above values. Due to space limitations and for the sake of simplicity, the present invention will no longer list them exhaustively.

[0012] Preferably, in the first coating layer, the mass ratio of sulfur element and graphene in the sulfur-doped graphene is (0.005-0.12):1, for example, it can be 0.005:1, 0.01:1, 0.03:1, 0.05:1, 0.08:1, 0.1:1 or 0.12:1, as well as specific point values ​​between the above values. Due to space limitations and for the sake of simplicity, the present invention will no longer list them exhaustively.

[0013] Preferably, the first coating layer further includes an auxiliary agent, and the auxiliary agent includes a conductive polymer and / or a carbonized product of a conductive polymer;

[0014] Preferably, the conductive polymer comprises at least one of polypyrrole, polyaniline, polythiophene or polyethylene oxide, or at least one of copolymers formed by at least two of the monomers of polypyrrole, polyaniline, polythiophene and polyethylene oxide, or a combination of at least one of the polypyrrole, polyaniline, polythiophene and polyethylene oxide and at least one of the copolymers;

[0015] Preferably, in the first coating layer, the mass ratio of the sulfur-doped graphene to the auxiliary agent is 1:(3-7), for example, it can be 1:3, 1:4, 1:5, 1:6 or 1:7, as well as specific point values ​​between the above values. Due to space limitations and for the sake of simplicity, the present invention will no longer list them exhaustively.

[0016] Preferably, based on the total mass of the sodium ion battery phosphate positive electrode material as 100%, the mass fraction of the second coating layer is 0.5-20%, for example, it can be 0.5%, 1%, 3%, 5%, 8%, 10%, 13%, 15%, 18% or 20%, as well as specific point values ​​between the above values. Due to space limitations and for the sake of simplicity, the present invention will no longer list them exhaustively.

[0017] Preferably, in the second coating layer, the mass fraction of the nitrogen element in the nitrogen and phosphorus co-doped carbon material is 0.01-0.8%, for example, it can be 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7% or 0.8%, as well as specific point values ​​between the above values. Due to space limitations and for the sake of simplicity, the present invention will no longer list them exhaustively.

[0018] Preferably, in the second coating layer, the mass fraction of the phosphorus element in the nitrogen and phosphorus co-doped carbon material is 0.01-1%, for example, it can be 0.01%, 0.03%, 0.05%, 0.08%, 0.1%, 0.3%, 0.5%, 0.8% or 1%, as well as specific point values ​​between the above values. Due to space limitations and for the sake of simplicity, the present invention will no longer list them exhaustively.

[0019] Preferably, the sodium ion battery phosphate positive electrode material also includes a nitrogen-doped oxygen-containing compound, and the nitrogen-doped oxygen-containing compound ion-dopes the sodium ion battery phosphate positive electrode material. The introduction of the nitrogen element can form a synergistic effect with the P and S elements in the first coating layer and the first carbon source and the second carbon source of the second coating layer, and various combinations of chemical bonds are formed between the five elements N, P, S, C, and O inside and on the surface of the sodium ion battery phosphate positive electrode material, for example, NO, NP, NS, NPC, NSC, PNO, SNO, CNO, etc. can be formed. The formation of these chemical bonds can well repair the lattice interface of the phosphate positive electrode material (such as sodium vanadium phosphate positive electrode material), effectively prevent the dissolution of transition metal ions in the electrolyte, enhance the cycle life and cycle stability of the positive electrode material, and improve the electrochemical performance of the material.

[0020] Preferably, the mass fraction of nitrogen in the nitrogen-doped oxygen-containing compound is 0.01-0.8%, for example, it can be 0.01%, 0.03%, 0.05%, 0.07%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, or 0.8%.

[0021] Preferably, based on the total mass of the sodium ion battery phosphate positive electrode material as 100%, the mass fraction of the nitrogen-doped oxygen-containing compound is 0.1-5%, for example, it can be 0.1%, 0.3%, 0.5%, 0.8%, 1%, 2%, 3%, 4% or 5%, as well as specific point values ​​between the above values. Due to space limitations and for the sake of simplicity, the present invention will no longer list them exhaustively.

[0022] Preferably, the oxygen-containing compound in the nitrogen-doped oxygen-containing compound includes doped boron phosphate, and the doped boron phosphate is boron phosphate doped with sodium and / or potassium;

[0023] Preferably, the chemical formula of the sodium and / or potassium doped boron phosphate is Na m K n B 1-x / 3 PO4, wherein m+n=x, 0.01≤x<0.15, for example, it can be 0.01%, 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45% or 0.5%, as well as specific point values ​​between the above values. Due to space limitations and for the sake of simplicity, the present invention will no longer list them exhaustively.

[0024] Preferably, the nitrogen-doped oxygen-containing compound further comprises at least one of zinc oxide, copper oxide, cuprous oxide, magnesium oxide, vanadium oxide and metatitanic acid;

[0025] Preferably, the oxygen-containing compound in the nitrogen-doped oxygen-containing compound includes a composition of at least one of zinc oxide, copper oxide, cuprous oxide, magnesium oxide, vanadium oxide and titanic acid and the boron phosphate doped with sodium and / or potassium, and the mass proportion of the boron phosphate doped with sodium and / or potassium in the composition is more than 50%, for example, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 90%, 95%, 96%, 98% or 99%.

[0026] In a second aspect, the present invention provides a method for preparing the sodium ion battery phosphate positive electrode material as described in the first aspect, the preparation method comprising the following steps:

[0027] (1) mixing a first carbon source, a metal source, a phosphorus source, oxalic acid and a template to obtain a mixture;

[0028] (2) After calcining the mixture described in step (1), the template is removed to obtain a mesoporous phosphate precursor coated with the first carbon source in situ;

[0029] (3) mixing the mesoporous phosphate precursor in situ coated with the first carbon source described in step (2) with a sodium source and a second carbon source, sand-milling, spray drying, and calcining to obtain the sodium ion battery phosphate positive electrode material;

[0030] Wherein, the first carbon source includes sulfur-doped graphene, and the second carbon source includes nitrogen and phosphorus co-doped carbon material.

[0031] The method of the present invention adopts two different carbon sources to perform in-situ coating in two steps to obtain a precursor, and then calcined with sodium to obtain a sodium ion battery phosphate positive electrode material. A coating layer with excellent structure and performance is formed on the surface of the positive electrode material. The carbon coating method of the present invention is significantly different from the existing traditional carbon coating method. On the one hand, the method provided by the present invention has more uniform coating and better conductivity; on the other hand, the composition of the two carbon sources is different from that of the traditional carbon source. Among the two types of carbon sources in the present invention, the first carbon source includes sulfur-doped graphene, and the second carbon source includes nitrogen and phosphorus co-doped carbon material. The addition of these two types of carbon sources can effectively inhibit the dissolution of active substances in the electrolyte, prevent the structural collapse of the positive electrode material, and help improve the rate performance and cycle stability of the positive electrode material.

[0032] The entire process of the preparation method of the present invention is simple and easy to implement, and is conducive to large-scale promotion.

[0033] The present invention does not specifically limit the preparation method of sulfur-doped graphene. It is exemplary but not restrictive. It can be prepared according to the following method, which specifically includes the following steps:

[0034] (a) mixing a sulfur source and graphene, and reacting them at 100-300° C. and 1-20 MPa to obtain a precursor;

[0035] (b) The precursor is heat treated to obtain sulfur-doped graphene.

[0036] In the above method, in step (a), the reaction temperature can be, for example, 100°C, 120°C, 150°C, 180°C, 200°C, 220°C, 230°C, 260°C, 280°C or 300°C. The reaction pressure can be, for example, 1 MPa, 3 MPa, 5 MPa, 7 MPa, 9 MPa, 10 MPa, 12 MPa, 14 MPa, 15 MPa, 17 MPa, 18 MPa or 20 MPa.

[0037] Preferably, in step (a), the sulfur source is at least one of sodium sulfide, sodium thiosulfate, thiourea, thiol, thiophenol, thioether, disulfide, polysulfide, cyclic sulfide, diallyl sulfide, diallyl thiosulfonate, diallyl trisulfide or diallyl disulfide, preferably thiourea, or a combination of thiourea and at least one of thiol, thiophenol, thioether, disulfide, polysulfide, cyclic sulfide, diallyl sulfide, diallyl thiosulfonate, diallyl trisulfide or diallyl disulfide.

[0038] Preferably, in step (a), the reaction time is 1-36 h, for example, it can be 1 h, 2 h, 5 h, 6 h, 8 h, 10 h, 15 h, 18 h, 20 h, 22 h, 24 h, 26 h, 30 h, 33 h or 36 h.

[0039] Preferably, after the reaction in step (a) is completed, the obtained product is cooled, washed and dried to obtain a precursor.

[0040] Preferably, the heat treatment in step (b) is performed under a protective atmosphere, and the gas in the protective atmosphere comprises at least one of helium, argon or nitrogen.

[0041] Preferably, the temperature of the heat treatment in step (b) is 500-1000°C, for example, 500°C, 600°C, 650°C, 700°C, 800°C, 900°C or 1000°C.

[0042] Preferably, the heat treatment time in step (b) is 1-30 h, for example, 1 h, 3 h, 5 h, 8 h, 10 h, 12 h, 15 h, 18 h, 20 h, 22 h, 24 h, 26 h, 28 h or 30 h.

[0043] The present invention does not specifically limit the preparation method of nitrogen and phosphorus co-doped carbon materials. By way of example and not limitation, the preparation method can be carried out according to the following method, which specifically includes the following steps:

[0044] (A) placing the carbon material in an ammonia atmosphere, and then heating it to 700-950° C. for nitriding to obtain a nitrided carbon material;

[0045] (B) The nitrided carbon material is mixed with a phosphorus source, reacted under conditions of 130-280° C. and 1-6 MPa, and then the resulting product is heat treated to obtain the nitrogen and phosphorus co-doped carbon material.

[0046] In the above method, the temperature of step (A) can be, for example, 700°C, 750°C, 800°C, 850°C, 900°C or 950°C.

[0047] Preferably, the carbon material in step (A) includes at least one of polyvinyl alcohol, acetylene black, carbon fiber, graphene, polyethylene glycol, soluble starch, coal tar, carbon black, dextrin, coke, citric acid, cellulose, glucose, single crystal / polycrystalline rock sugar, sucrose, fructose or carbon nanotubes.

[0048] Preferably, the heating rate in step (A) is 1-10°C / min, for example, it can be 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 8°C / min or 10°C / min, etc.

[0049] Preferably, the nitriding treatment time of step (A) is 1-8 hours, for example, it can be 1 hour, 2 hours, 3 hours, 5 hours, 6 hours, 7 hours or 8 hours.

[0050] Preferably, after step (A) and before step (B), the nitrided carbon material is ground and passed through a 200-mesh sieve.

[0051] In the above method, the reaction temperature of step (B) can be, for example, 130°C, 150°C, 160°C, 170°C, 180°C, 200°C, 220°C, 240°C, 260°C or 280°C.

[0052] In the above method, the reaction pressure of step (B) can be, for example, 1 MPa, 2 MPa, 3 MPa, 4 MPa, 5 MPa or 6 MPa.

[0053] Preferably, the phosphorus source in step (B) comprises any one of elemental phosphorus, an organic phosphorus compound or an inorganic phosphorus compound, or a mixture of at least two thereof, preferably an organic phosphorus compound, and more preferably at least one of tripolychlorophosphazene, adenosine triphosphate, adenosine diphosphate, phosphoenonepyruvate, phosphate ester, tetrakishydroxymethylphosphonium chloride, vinyl dimethyl phosphate, hexachlorocyclotriphosphazene, polydichlorophosphazene, polyalkoxyphosphazene, polyaryloxyphosphazene or polyfluoroepoxyphosphazene.

[0054] Preferably, the reaction time of step (B) is 1-24 h, for example, it can be 1 h, 3 h, 5 h, 7 h, 8 h, 10 h, 12 h, 15 h, 16 h, 18 h, 20 h, 22 h or 24 h, etc.

[0055] Preferably, after the reaction in step (B) and before the heat treatment, the reaction product is subjected to the steps of cooling, washing and drying.

[0056] Preferably, the temperature of the heat treatment in step (B) is 550-1050°C, for example, it can be 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C or 1050°C.

[0057] Preferably, the heat treatment time in step (B) is 1-30 h, for example, it can be 1 h, 2 h, 3 h, 5 h, 7 h, 8 h, 10 h, 13 h, 16 h, 18 h, 20 h, 25 h or 30 h.

[0058] Preferably, the heat treatment in step (B) is followed by washing and drying.

[0059] As a preferred technical solution of the preparation method of the present invention, the mass ratio of sulfur to graphene in the sulfur-doped graphene is (0.005-0.12):1.

[0060] Preferably, in step (1), the first carbon source further comprises a conductive polymer;

[0061] Preferably, the metal source in step (1) is a vanadium source, and the prepared phosphate positive electrode material is a sodium vanadium phosphate positive electrode material;

[0062] Preferably, the vanadium source includes at least one of V2O5, V2O3, NH4VO3 or VOC2O4;

[0063] Preferably, the phosphorus source in step (1) comprises at least one of sodium phosphate, potassium phosphate, triammonium phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, sodium dihydrogen phosphate, dipotassium hydrogen phosphate, potassium dihydrogen phosphate, disodium hydrogen phosphate, iron phosphate, manganese phosphate, lithium phosphate, lithium dihydrogen phosphate or phosphoric acid;

[0064] Preferably, the template in step (1) comprises at least one of SBA-15, KIT-6 or mesoporous carbon;

[0065] Preferably, in step (1), the molar ratio of the metal source, oxalic acid and template is 1:(2-8):(0.1-12), wherein the selection range of oxalic acid "2-8" can be, for example, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5 or 8, and the selection range of the template "0.1-12" can be, for example, 0.1, 0.3, 0.5, 1, 1.5, 2, 3, 3.5, 4, 5, 6, 7, 8, 9, 10, 11 or 12, as well as specific point values ​​between the above values, are no longer exhaustively listed in the present invention due to space limitations and for the sake of simplicity.

[0066] Preferably, after the mixing in step (1), ultrasonic treatment and drying are performed to obtain a dry mixture;

[0067] Preferably, the temperature of the ultrasonic treatment is 25-100°C, for example, it can be 25°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C or 100°C, as well as specific point values ​​between the above values. Due to space limitations and for the sake of simplicity, the present invention will no longer list them exhaustively.

[0068] Preferably, the power of the ultrasonic treatment is 30-200 W, for example, 30 W, 50 W, 80 W, 100 W, 130 W, 150 W, 180 W or 200 W, as well as specific point values ​​between the above values, which are no longer exhaustively listed in the present invention due to space limitations and for the sake of simplicity.

[0069] Preferably, the ultrasonic treatment time is 1-10 h, for example, it can be 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h or 10 h, as well as specific point values ​​between the above values. Due to space limitations and for the sake of simplicity, the present invention will no longer list them exhaustively.

[0070] As a preferred technical solution of the preparation method of the present invention, the calcination in step (2) is carried out in a protective atmosphere, and the gas in the protective atmosphere includes at least one of argon, helium or nitrogen;

[0071] Preferably, the calcination temperature in step (2) is 150-650°C, for example, it can be 150°C, 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C or 650°C, as well as specific point values ​​between the above values. Due to space limitations and for the sake of simplicity, the present invention will no longer list them exhaustively.

[0072] Preferably, the calcination time in step (2) is 1-30 h, for example, 1 h, 5 h, 10 h, 15 h, 20 h, 25 h or 30 h, as well as specific point values ​​between the above values, which are no longer exhaustively listed in the present invention due to space limitations and for the sake of simplicity.

[0073] Preferably, the method for removing the template in step (2) is: using an alkaline solution to perform an alkali dissolution treatment on the calcined product to remove the template;

[0074] Preferably, the alkali in the alkaline solution comprises sodium hydroxide and / or potassium hydroxide;

[0075] Preferably, the temperature of the alkali dissolution treatment is 25-120°C, for example, it can be 25°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C or 120°C, as well as specific point values ​​between the above values. Due to space limitations and for the sake of simplicity, the present invention will no longer list them exhaustively.

[0076] Preferably, the alkaline dissolution treatment is followed by washing and drying steps, and the detergent used for washing is water.

[0077] As a preferred technical solution of the preparation method of the present invention, the sodium source in step (3) includes at least one of sodium chloride, sodium bromide, sodium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium sulfate, sodium carbonate, sodium hydroxide, sodium acetate, sodium nitrate, sodium oxalate, sodium formate, sodium tert-butoxide, sodium benzoate or sodium citrate;

[0078] Preferably, the vanadium source, phosphorus source and sodium source are added according to the ratio of each element in the chemical formula Na3V2(PO4)3;

[0079] Preferably, in step (3), the second carbon source also includes a nitrogen-doped oxygen-containing compound.

[0080] The present invention does not specifically limit the preparation method of the nitrogen-doped oxygen-containing compound. By way of example and not limitation, the preparation can be carried out according to the following method, which specifically includes the following steps:

[0081] (I) mixing an oxygen-containing compound and a nitrogen source, reacting them at 100-280° C. and 1-20 MPa to obtain a precursor;

[0082] (II) After the reaction is completed, the obtained product is cooled, washed, and dried, and then heated to 550-1100° C. in argon and / or nitrogen for heat treatment for 1-30 hours to obtain the nitrogen-doped oxygen-containing compound.

[0083] In the above method, the reaction temperature in step (I) can be, for example, 100°C, 120°C, 140°C, 160°C, 180°C, 200°C, 230°C, 260°C or 280°C.

[0084] In the above method, the pressure of the reaction in step (I) can be, for example, 1 MPa, 2 MPa, 3 MPa, 5 MPa, 7 MPa, 9 MPa, 10 MPa, 12 MPa, 15 MPa, 18 MPa or 20 MPa.

[0085] Preferably, the reaction time of step (I) can be, for example, 1h, 3h, 8h, 10h, 15h, 20h, 25h, 30h, 35h, 40h, 45h, 50h, 55h, 60h, 65h, 70h or 72h, etc. Preferably, the nitrogen source of step (I) comprises at least one of thiourea, urea, amino acid, acetamide, benzylamine, melamine, polyacrylonitrile or polypyrrole.

[0086] Preferably, the oxygen-containing compound in step (I) is boron phosphate doped with sodium or potassium, or a combination of at least one of zinc oxide, copper oxide, cuprous oxide, magnesium oxide, vanadium oxide, metatitanic acid and boron phosphate doped with sodium or potassium.

[0087] Preferably, the chemical formula of the sodium or potassium doped boron phosphate is Na m K n B 1-x / 3 PO4, wherein m+n=x, 0.01≤x<0.15.

[0088] Preferably, the particle size D50 of the material after sand grinding in step (3) is 250-650 nm, for example, it can be 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, 500 nm, 550 nm, 600 nm or 650 nm, as well as specific point values ​​between the above values. Due to space limitations and for the sake of simplicity, the present invention will no longer list them exhaustively.

[0089] Preferably, the sand milling in step (3) is carried out in a solvent, and the solvent includes at least one of water, isopropanol, ethylene glycol, acetone, tetrahydrofuran, ether, benzene, toluene or dimethylformamide;

[0090] Preferably, the spray drying temperature in step (3) is 25-220°C, for example, it can be 25°C, 50°C, 80°C, 100°C, 130°C, 150°C, 180°C, 200°C or 220°C, as well as specific point values ​​between the above values. Due to space limitations and for the sake of simplicity, the present invention will no longer list them exhaustively.

[0091] Preferably, the calcination in step (3) is carried out in a protective atmosphere, and the gas in the protective atmosphere comprises at least one of argon, helium or nitrogen.

[0092] Preferably, the calcination temperature in step (3) is 500-1050°C, for example, it can be 500°C, 600°C, 700°C, 800°C, 900°C, 1000°C or 1050°C, as well as specific point values ​​between the above values. Due to space limitations and for the sake of simplicity, the present invention will no longer list them exhaustively.

[0093] Preferably, the calcination time in step (3) is 1-24 h, for example, 1 h, 4 h, 8 h, 12 h, 16 h, 20 h or 24 h, as well as specific point values ​​between the above values, which are not exhaustively listed in the present invention due to space limitations and for the sake of simplicity.

[0094] Preferably, after the calcination in step (3) is completed, cooling and crushing and classification are performed, wherein the cooling method may be natural cooling.

[0095] In a third aspect, the present invention provides a sodium ion battery, characterized in that the sodium ion battery comprises the sodium ion battery phosphate positive electrode material described in the first aspect.

[0096] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0097] Compared with the prior art, the present invention has the following beneficial effects:

[0098] (1) The present invention sequentially arranges a first coating layer comprising sulfur-doped graphene and a second coating layer comprising nitrogen and phosphorus co-doped carbon material on the surface of a phosphate core, and the sodium ion battery phosphate positive electrode material has a mesoporous structure, which can effectively improve the conductivity, inhibit the dissolution of active substances in the electrolyte, prevent the collapse of the positive electrode material structure, and help improve the rate performance and cycle stability of the positive electrode material.

[0099] (2) The battery assembled with the sodium ion battery phosphate positive electrode material of the present invention has a high conductivity at 0.1A g -1 At a current density of 1.34 mAh g, the reversible specific capacity after 100 cycles can reach 111.4 mAh g -1 .

[0100] (3) The entire process of the preparation method of the present invention is simple and easy to implement, which is conducive to large-scale promotion. DETAILED DESCRIPTION

[0101] The technical solution of the present invention is further illustrated below through specific implementation methods.

[0102] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0103] To facilitate understanding of the present invention, the technical solution of the present invention is further described below through specific implementation methods.

[0104] As a preferred technical solution, the sulfur-doped graphene used in each embodiment of the present invention is prepared according to the following method:

[0105] A sulfur source and graphene are mixed in proportion, reacted at 100-300° C. and 1-20 MPa for 1-36 h, the resulting product is cooled, washed, and dried to obtain a sulfur-doped graphene precursor, and then the resulting precursor is heated to 500-1000° C. in an argon and / or nitrogen atmosphere for heat treatment for 1-30 h, and the sulfur-doped graphene is obtained after washing and drying.

[0106] In one embodiment, the sulfur source is any one of sodium sulfide, sodium thiosulfate, thiourea, thiol, thiophenol, thioether, disulfide, polysulfide, cyclic sulfide, diallyl sulfide, diallyl thiosulfonate, diallyl trisulfide or diallyl disulfide, or a combination of at least two thereof, preferably thiourea, or thiourea and at least one of thiol, thiophenol, thioether, disulfide, polysulfide, cyclic sulfide, diallyl sulfide, diallyl thiosulfonate, diallyl trisulfide or diallyl disulfide.

[0107] In one embodiment, the mass ratio of sulfur to graphene in the sulfur-doped graphene is (0.005-0.12):1.

[0108] As a preferred technical solution, the nitrogen-doped oxygen-containing compound used in each embodiment of the present invention is prepared according to the following method:

[0109] The oxygen-containing compound and the nitrogen source are mixed in proportion, and reacted at 100-280° C. and 1-20 MPa for 1-72 hours. After the reaction, the obtained product is cooled, washed, and dried, and then heated to 550-1100° C. in argon and / or nitrogen for heat treatment for 1-30 hours to obtain the nitrogen-doped oxygen-containing compound.

[0110] In one embodiment, the nitrogen source is at least one of thiourea, urea, amino acid, acetamide, benzylamine, melamine, polyacrylonitrile or polypyrrole.

[0111] In one embodiment, the oxygen-containing compound is sodium- or potassium-doped boron phosphate, or a combination of at least one of zinc oxide, copper oxide, cuprous oxide, magnesium oxide, vanadium oxide, metatitanic acid and sodium- or potassium-doped boron phosphate.

[0112] In one embodiment, the chemical formula of the sodium or potassium doped boron phosphate is Na m K n B 1-x / 3 PO4, wherein m+n=x, 0.01≤x<0.15.

[0113] In one embodiment, the mass fraction of nitrogen in the nitrogen-doped oxygen-containing compound is 0.01-0.5%.

[0114] As a preferred technical solution, the nitrogen and phosphorus co-doped carbon material used in each embodiment of the present invention is prepared according to the following method:

[0115] The carbon material is placed in an ammonia atmosphere, and then heated to 700-950° C. at a rate of 1-10° C. / min for nitridation treatment for 1-8 hours, ground through a 200-mesh sieve and mixed with a phosphorus source, reacted at 130-280° C. and 1-6 MPa for 1-24 hours, cooled, washed and dried, and the resulting product is heated to 550-1050° C. for heat treatment for 1-30 hours, washed and dried to obtain the nitrogen and phosphorus co-doped carbon material;

[0116] In one embodiment, the phosphorus source for preparing the nitrogen and phosphorus co-doped carbon material is any one of elemental phosphorus, an organic phosphorus compound or an inorganic phosphorus compound, or a mixture of at least two of them, preferably an organic phosphorus compound, and more preferably at least one of tripolychlorophosphazene, adenosine triphosphate, adenosine diphosphate, phosphoenonepyruvate, phosphate ester, tetrakishydroxymethylphosphonium chloride, vinyl dimethyl phosphate, hexachlorocyclotriphosphazene, polydichlorophosphazene, polyalkoxyphosphazene, polyaryloxyphosphazene or polyfluoroepoxyphosphazene.

[0117] In one embodiment, the carbon material for preparing the nitrogen and phosphorus co-doped carbon material is at least one of polyvinyl alcohol, acetylene black, carbon fiber, graphene, polyethylene glycol, soluble starch, coal tar, carbon black, dextrin, coke, citric acid, cellulose, glucose, single crystal / polycrystalline rock sugar, sucrose, fructose or carbon nanotubes.

[0118] In one embodiment, the mass fraction of nitrogen in the nitrogen and phosphorus co-doped carbon material is 0.01-0.8%.

[0119] In one embodiment, the mass fraction of phosphorus in the nitrogen and phosphorus co-doped carbon material is 0.01-1%.

[0120] Typical but non-limiting embodiments of the present invention are as follows:

[0121] Example 1

[0122] A sodium ion battery phosphate positive electrode material, the phosphate positive electrode material having a mesoporous structure, comprising a phosphate core and a first coating layer and a second coating layer sequentially coated from the core to the outside, the first coating layer comprising sulfur-doped graphene and polypyrrole and / or a carbonized product of polypyrrole, the second coating layer comprising nitrogen-phosphorus co-doped carbon material, and the sodium ion battery phosphate positive electrode material further comprising a nitrogen-doped oxygen-containing compound;

[0123] Wherein, based on the total mass of the sodium ion battery phosphate positive electrode material as 100%, the mass fraction of the first coating layer is 2%, the mass ratio of the mass of sulfur-doped graphene to the mass of polypyrrole and / or the carbonization product of polypyrrole in the first coating layer is 1:7, and the mass ratio of sulfur element to graphene in the sulfur-doped graphene is 0.05:1;

[0124] Based on the total mass of the sodium ion battery phosphate positive electrode material as 100%, the mass fraction of the second coating layer is 5%, the mass fraction of the nitrogen element in the nitrogen and phosphorus co-doped carbon material is 0.1%, and the mass fraction of the phosphorus element in the nitrogen and phosphorus co-doped carbon material is 0.3%;

[0125] Based on the total mass of the sodium ion battery phosphate positive electrode material being 100%, the mass fraction of the nitrogen-doped oxygen-containing compound is 5%, the mass fraction of the nitrogen element in the nitrogen-doped oxygen-containing compound is 0.05%, and the chemical formula of the oxygen-containing compound is Na 0.06 B 0.98 PO4.

[0126] The preparation method of the sodium ion battery phosphate positive electrode material of this embodiment comprises the following steps:

[0127] (1) mixing a first carbon source, V2O5, potassium phosphate, a template agent SBA-15 and oxalic acid, controlling the molar ratio of V2O5, oxalic acid and the template agent to be 1:3:1, ultrasonically treating at 25°C at a power of 200 W for 1 h, and drying to obtain a dry mixture;

[0128] (2) heating the dried mixture obtained in step (1) to 650° C. and calcining for 1 h, then adding a sodium hydroxide solution at 50° C. to remove the template, thereby obtaining a mesoporous vanadium phosphate in-situ coated with the first carbon source;

[0129] (3) mixing the mesoporous vanadium phosphate in situ coated with the first carbon source obtained in step (2) with lithium nitrate, nitrogen-doped oxygen-containing compound and the second carbon source, adding an appropriate amount of deionized water and sand-milling the slurry until the particle size D50 is 300 nm, and spray-drying the slurry at 150° C. after sand-milling to obtain a positive electrode material precursor;

[0130] (4) The cathode material precursor obtained in step (3) is heated to 950° C. and calcined for 3 h, and then naturally cooled to obtain a coated sodium vanadium phosphate cathode material, i.e., a coated sodium vanadium phosphate cathode material.

[0131] In the above preparation process, the ingredients are prepared according to the ratio of each element in the chemical formula Na3V2(PO4)3, the first carbon source is a mixture of sulfur-doped graphene and polypyrrole, the second carbon source is a nitrogen-phosphorus co-doped carbon material, and the nitrogen-doped oxygen-containing compound (wherein the oxygen-containing compound is Na 0.06 B 0.98 PO4).

[0132] After testing, at 0.1A g -1 At a current density of 1.34 W, the reversible specific capacity after 100 cycles is 107.1 mAh g -1 .

[0133] Example 2

[0134] A sodium ion battery phosphate positive electrode material, the phosphate positive electrode material having a mesoporous structure, comprising a phosphate core and a first coating layer and a second coating layer sequentially coated from the core to the outside, the first coating layer comprising sulfur-doped graphene and a conductive polymer and / or a carbonized product of the conductive polymer, the second coating layer comprising a nitrogen-phosphorus co-doped carbon material, and the sodium ion battery phosphate positive electrode material further comprising a nitrogen-doped oxygen-containing compound;

[0135] Wherein, based on the total mass of the sodium ion battery phosphate positive electrode material as 100%, the mass fraction of the first coating layer is 0.7%, the mass ratio of sulfur-doped graphene to the conductive polymer in the first coating layer is 1:4, and the mass ratio of sulfur element to graphene in the sulfur-doped graphene is 0.12:1;

[0136] Based on the total mass of the sodium ion battery phosphate positive electrode material as 100%, the mass fraction of the second coating layer is 8%, the mass fraction of the nitrogen element in the nitrogen and phosphorus co-doped carbon material is 0.2%, and the mass fraction of the phosphorus element in the nitrogen and phosphorus co-doped carbon material is 0.08%;

[0137] Based on the total mass of the sodium ion battery phosphate positive electrode material being 100%, the mass fraction of the nitrogen-doped oxygen-containing compound is 1.5%, the mass fraction of the nitrogen element in the nitrogen-doped oxygen-containing compound is 0.3%, and the oxygen-containing compound is copper oxide and K 0.03 B 0.99 PO4 mixture, in which K 0.03 B 0.99 PO4 accounts for 60% by mass.

[0138] The preparation method of the sodium ion battery phosphate positive electrode material of this embodiment comprises the following steps:

[0139] (1) mixing a first carbon source, NH4VO3, sodium phosphate, a template agent KIT-6 and oxalic acid, controlling the molar ratio of NH4VO3, oxalic acid and the template agent to be 1:4.5:0.8, performing ultrasonic treatment at 100°C with a power of 30 W and drying for 10 hours to obtain a dry mixture;

[0140] (2) heating the dried mixture obtained in step (1) to 450° C. and calcining for 16 h, then adding a sodium hydroxide solution at 80° C. to remove the template, thereby obtaining a mesoporous vanadium phosphate in situ coated with the first carbon source;

[0141] (3) mixing the mesoporous vanadium phosphate in situ coated with the first carbon source obtained in step (2) with lithium oxalate, nitrogen-doped oxygen-containing compound and the second carbon source, adding an appropriate amount of ethylene glycol and sand-milling the slurry until the particle size D50 is 500 nm, and spray-drying at 160° C. after sand-milling to obtain a positive electrode material precursor;

[0142] (4) The cathode material precursor obtained in step (3) is heated to 800° C. and calcined for 12 h, and then naturally cooled to obtain the coated sodium vanadium phosphate cathode material.

[0143] In the above preparation process, the ingredients are prepared according to the ratio of each element in the chemical formula K3V2(PO4)3, the first carbon source is a mixture of sulfur-doped graphene and polypyrrole, the second carbon source is a nitrogen-phosphorus co-doped carbon material, and the nitrogen-doped oxygen-containing compound (wherein the oxygen-containing compound is copper oxide and K 0.03 B 0.99 PO4).

[0144] After testing, at 0.1A g -1 At a current density of 1.34 W, the reversible specific capacity after 100 cycles is 109.6 mAh g -1 .

[0145] Example 3

[0146] A sodium ion battery phosphate positive electrode material, the phosphate positive electrode material having a mesoporous structure, comprising a phosphate core and a first coating layer and a second coating layer sequentially coated from the core to the outside, the first coating layer comprising sulfur-doped graphene and a conductive polymer and / or a carbonized product of the conductive polymer, the second coating layer comprising a nitrogen-phosphorus co-doped carbon material, and the sodium ion battery phosphate positive electrode material further comprising a nitrogen-doped oxygen-containing compound;

[0147] Wherein, based on the total mass of the sodium ion battery phosphate positive electrode material being 100%, the mass fraction of the first coating layer is 10%, in the first coating layer, the mass ratio of sulfur-doped graphene to the conductive polymer is 1:6, and the mass ratio of sulfur element to graphene in the sulfur-doped graphene is 0.01:1;

[0148] Based on the total mass of the sodium ion battery phosphate positive electrode material as 100%, the mass fraction of the second coating layer is 1%, the mass fraction of the nitrogen element in the nitrogen and phosphorus co-doped carbon material is 0.8%, and the mass fraction of the phosphorus element in the nitrogen and phosphorus co-doped carbon material is 0.5%;

[0149] Based on the total mass of the sodium ion battery phosphate positive electrode material as 100%, the mass fraction of the nitrogen-doped oxygen-containing compound is 0.1%, the mass fraction of the nitrogen element in the nitrogen-doped oxygen-containing compound is 0.5%, and the chemical formula of the oxygen-containing compound is Na 0.09 B 0.97 PO4.

[0150] The preparation method of the sodium ion battery phosphate positive electrode material of this embodiment comprises the following steps:

[0151] (1) mixing a first carbon source, V2O3, triammonium phosphate, a template agent SBA-15 and oxalic acid, controlling the molar ratio of V2O3, oxalic acid and the template agent to be 1:5:3, ultrasonically treating at 80°C with a power of 120 W for 5 h, and drying the mixture to obtain a dry mixture;

[0152] (2) heating the dried mixture obtained in step (1) to 350° C. and calcining for 14 h, then adding a potassium hydroxide solution at 100° C. to remove the template, thereby obtaining a mesoporous vanadium phosphate in-situ coated with the first carbon source;

[0153] (3) mixing the mesoporous vanadium phosphate in situ coated with the first carbon source obtained in step (2) with lithium formate, a nitrogen-doped oxygen-containing compound and a second carbon source, adding an appropriate amount of deionized water and sand-milling the mixture until the particle size D50 of the slurry is 400 nm, and spray-drying the mixture at 180° C. after sand-milling to obtain a positive electrode material precursor;

[0154] (4) The cathode material precursor obtained in step (3) is heated to 1000° C. and calcined for 2 h, and then naturally cooled to obtain the coated sodium vanadium phosphate cathode material.

[0155] In the above preparation process, the ingredients are prepared according to the ratio of each element in the chemical formula Na3V2(PO4)3, the first carbon source is a mixture of sulfur-doped graphene and polypyrrole, the second carbon source is a nitrogen-phosphorus co-doped carbon material, and the nitrogen-doped oxygen-containing compound (wherein the oxygen-containing compound is Na 0.09 B 0.97 PO4).

[0156] After testing, at 0.1A g -1 At a current density of 1.34 W, the reversible specific capacity after 100 cycles is 105.2 mAh g -1 .

[0157] Example 4

[0158] A sodium ion battery phosphate positive electrode material, the phosphate positive electrode material having a mesoporous structure, comprising a phosphate core and a first coating layer and a second coating layer sequentially coated from the core to the outside, the first coating layer comprising sulfur-doped graphene and a conductive polymer and / or a carbonized product of the conductive polymer, the second coating layer comprising a nitrogen-phosphorus co-doped carbon material, and the sodium ion battery phosphate positive electrode material further comprising a nitrogen-doped oxygen-containing compound;

[0159] Wherein, based on the total mass of the sodium ion battery phosphate positive electrode material as 100%, the mass fraction of the first coating layer is 0.5%, the mass ratio of sulfur-doped graphene to the conductive polymer in the first coating layer is 1:5, and the mass ratio of sulfur element to graphene in the sulfur-doped graphene is 0.1:1;

[0160] Based on the total mass of the sodium ion battery phosphate positive electrode material as 100%, the mass fraction of the second coating layer is 10%, the mass fraction of the nitrogen element in the nitrogen and phosphorus co-doped carbon material is 0.03%, and the mass fraction of the phosphorus element in the nitrogen and phosphorus co-doped carbon material is 0.05%;

[0161] Based on the total mass of the sodium ion battery phosphate positive electrode material being 100%, the mass fraction of the nitrogen-doped oxygen-containing compound is 3%, the mass fraction of the nitrogen element in the nitrogen-doped oxygen-containing compound is 0.02%, and the oxygen-containing compound is vanadium oxide and K 0.12 B 0.96 PO4 mixture, the K in the mixture 0.12 B 0.96 PO4 accounts for 80% by mass.

[0162] The preparation method of the sodium ion battery phosphate positive electrode material of this embodiment comprises the following steps:

[0163] (1) mixing a first carbon source, V2O5, potassium phosphate, a template mesoporous carbon and oxalic acid, controlling the molar ratio of V2O5, oxalic acid and the template to be 1:2:5, ultrasonically treating at 60°C with a power of 150 W for 3 h, and drying the mixture to obtain a dry mixture;

[0164] (2) heating the dried mixture obtained in step (1) to 500° C. and calcining for 10 h, then adding a potassium hydroxide solution at 80° C. to remove the template, thereby obtaining a mesoporous vanadium phosphate in-situ coated with the first carbon source;

[0165] (3) mixing the mesoporous vanadium phosphate in situ coated with the first carbon source obtained in step (2) with lithium oxalate, nitrogen-doped oxygen-containing compound and the second carbon source, adding an appropriate amount of ethylene glycol and sand-milling the slurry until the particle size D50 is 350 nm, and spray-drying at 150° C. after sand-milling to obtain a positive electrode material precursor;

[0166] (4) The cathode material precursor obtained in step (3) is heated to 650° C. and calcined for 20 h, and then naturally cooled to obtain the coated sodium vanadium phosphate cathode material.

[0167] In the above preparation process, the ingredients are prepared according to the ratio of each element in the chemical formula K3V2(PO4)3, the first carbon source is a mixture of sulfur-doped graphene and polypyrrole, the second carbon source is a nitrogen-phosphorus co-doped carbon material, and the nitrogen-doped oxygen-containing compound (wherein the oxygen-containing compound is vanadium oxide and K 0.12 B 0.96 PO4 mixture).

[0168] After testing, at 0.1A g -1 At a current density of 1.34 W, the reversible specific capacity after 100 cycles is 110.9 mAh g -1 .

[0169] Example 5

[0170] A sodium ion battery phosphate positive electrode material, the phosphate positive electrode material having a mesoporous structure, comprising a phosphate core and a first coating layer and a second coating layer sequentially coated from the core to the outside, the first coating layer comprising sulfur-doped graphene and a conductive polymer and / or a carbonized product of the conductive polymer, the second coating layer comprising a nitrogen-phosphorus co-doped carbon material, and the sodium ion battery phosphate positive electrode material further comprising a nitrogen-doped oxygen-containing compound;

[0171] Wherein, based on the total mass of the sodium ion battery phosphate positive electrode material as 100%, the mass fraction of the first coating layer is 2%, the mass ratio of sulfur-doped graphene to the conductive polymer in the first coating layer is 1:4, and the mass ratio of sulfur element to graphene in the sulfur-doped graphene is 0.08:1;

[0172] Based on the total mass of the sodium ion battery phosphate positive electrode material as 100%, the mass fraction of the second coating layer is 6%, the mass fraction of the nitrogen element in the nitrogen and phosphorus co-doped carbon material is 0.04%, and the mass fraction of the phosphorus element in the nitrogen and phosphorus co-doped carbon material is 0.06%;

[0173] Based on the total mass of the sodium ion battery phosphate positive electrode material being 100%, the mass fraction of the nitrogen-doped oxygen-containing compound is 2%, the mass fraction of the nitrogen element in the nitrogen-doped oxygen-containing compound is 0.1%, and the chemical formula of the oxygen-containing compound is Na 0.06 B 0.98 PO4.

[0174] The preparation method of the sodium ion battery phosphate positive electrode material of this embodiment comprises the following steps:

[0175] (1) mixing a first carbon source, VOC2O4, sodium phosphate, a template agent SBA-15 and oxalic acid, controlling the molar ratio of VOC2O4, oxalic acid and the template agent to be 1:6:3, ultrasonically treating at 50°C with a power of 100 W for 7 h, and drying to obtain a dry mixture;

[0176] (2) heating the dried mixture obtained in step (1) to 500° C. and calcining for 7 h, then adding a sodium hydroxide solution at 100° C. to remove the template, thereby obtaining a mesoporous vanadium phosphate in situ coated with the first carbon source;

[0177] (3) mixing the mesoporous vanadium phosphate in situ coated with the first carbon source obtained in step (2) with lithium hydroxide, a nitrogen-doped oxygen-containing compound and a second carbon source, adding an appropriate amount of deionized water and sand-milling the slurry until the particle size D50 is 250-650 nm, and spray-drying the slurry at 180° C. after sand-milling to obtain a positive electrode material precursor;

[0178] (4) The cathode material precursor obtained in step (3) is heated to 1050° C. and calcined for 1 hour, and then naturally cooled to obtain the coated sodium vanadium phosphate cathode material.

[0179] In the above preparation process, the ingredients are prepared according to the ratio of each element in the chemical formula Na3V2(PO4)3, the first carbon source is a mixture of sulfur-doped graphene and polypyrrole, the second carbon source is a nitrogen-phosphorus co-doped carbon material, and the nitrogen-doped oxygen-containing compound (wherein the oxygen-containing compound is Na 0.06 B 0.98 PO4).

[0180] After testing, at 0.1A g -1 At a current density of 1.34 mAh g, the reversible specific capacity after 100 cycles is 111.4 mAh g -1 .

[0181] Example 6

[0182] This embodiment provides a sodium ion battery phosphate positive electrode material, which is different from Embodiment 1 in that, based on the total mass of the sodium ion battery phosphate positive electrode material being 100%, the mass fraction of the first coating layer is 0.05%.

[0183] After testing, at 0.1A g -1 At a current density of 1.5 mAh g, the reversible specific capacity after 100 cycles is 91.5 mAh g -1 .

[0184] Example 7

[0185] This embodiment provides a sodium ion battery phosphate positive electrode material, which is different from Embodiment 1 in that, based on the total mass of the sodium ion battery phosphate positive electrode material being 100%, the mass fraction of the first coating layer is 11%.

[0186] After testing, at 0.1A g -1 At a current density of 1.34 W, the reversible specific capacity after 100 cycles is 93.2 mAh g -1 .

[0187] Example 8

[0188] This embodiment provides a sodium ion battery phosphate positive electrode material, which is different from Embodiment 1 in that the first coating layer does not include sulfur-doped graphene and polypyrrole and / or carbonization product of polypyrrole.

[0189] After testing, at 0.1A g -1 At a current density of 1.34 Å, the reversible specific capacity after 100 cycles is 101.8 mAh g -1 .

[0190] Example 9

[0191] This embodiment provides a sodium ion battery phosphate positive electrode material, which is different from Embodiment 1 in that, based on the total mass of the sodium ion battery phosphate positive electrode material being 100%, the mass fraction of the second coating layer is 0.4%.

[0192] After testing, at 0.1A g -1 At a current density of 1.5 Å, the reversible specific capacity after 100 cycles is 95 mAh g -1 .

[0193] Example 10

[0194] This embodiment provides a sodium ion battery phosphate positive electrode material, which is different from Embodiment 1 in that, based on the total mass of the sodium ion battery phosphate positive electrode material being 100%, the mass fraction of the second coating layer is 21%.

[0195] After testing, at 0.1A g -1 At a current density of 1.34 W, the reversible specific capacity after 100 cycles is 98.1 mAh g -1 .

[0196] Embodiment 11

[0197] This embodiment provides a sodium ion battery phosphate positive electrode material, which is different from Embodiment 1 in that, based on the total mass of the sodium ion battery phosphate positive electrode material being 100%, the mass fraction of the nitrogen-doped oxygen-containing compound is 0.05%.

[0198] After testing, at 0.1A g -1 At a current density of 1.34 mAh g, the reversible specific capacity after 100 cycles is 103.4 mAh g -1 .

[0199] Example 12

[0200] This embodiment provides a sodium ion battery phosphate positive electrode material, which is different from Embodiment 1 in that, based on the total mass of the sodium ion battery phosphate positive electrode material being 100%, the mass fraction of the nitrogen-doped oxygen-containing compound is 5.5%.

[0201] After testing, at 0.1A g -1 At a current density of 1.34 W, the reversible specific capacity after 100 cycles is 91.9 mAh g -1 .

[0202] Comparative Example 1

[0203] This embodiment provides a sodium ion battery phosphate positive electrode material, which is different from Embodiment 1 in that the sodium ion battery phosphate positive electrode material does not contain a first coating layer.

[0204] After testing, at 0.1A g -1 At a current density of 1.3 mAh g, the reversible specific capacity after 100 cycles is 84.3 mAh g -1 .

[0205] Comparative Example 2

[0206] This embodiment provides a sodium ion battery phosphate positive electrode material, which is different from Embodiment 1 in that the sodium ion battery phosphate positive electrode material does not contain a second coating layer.

[0207] After testing, at 0.1A g -1 At a current density of 1.34 mAh g, the reversible specific capacity after 100 cycles is 81.4 mAh g -1 . The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, the equivalent replacement of the raw materials of the product of the present invention, the addition of auxiliary ingredients, the selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A sodium ion battery phosphate positive electrode material, characterized in that: The phosphate positive electrode material has a mesoporous structure, and includes a phosphate core and a first coating layer and a second coating layer sequentially coated from the core to the outside, wherein the first coating layer includes sulfur-doped graphene, and the second coating layer includes nitrogen and phosphorus co-doped carbon material.

2. The sodium ion battery phosphate positive electrode material according to claim 1, characterized in that: Based on the total mass of the sodium ion battery phosphate positive electrode material as 100%, the mass fraction of the first coating layer is 0.1-10%; Preferably, in the first coating layer, the mass ratio of sulfur element in the sulfur-doped graphene to graphene is (0.005-0.12):

1.

3. The sodium ion battery phosphate positive electrode material according to claim 1 or 2, characterized in that: The first coating layer also includes an auxiliary agent, which includes a conductive polymer and / or a carbonized product of a conductive polymer; Preferably, the conductive polymer comprises at least one of polypyrrole, polyaniline, polythiophene or polyethylene oxide, or at least one of copolymers formed by at least two of the monomers of polypyrrole, polyaniline, polythiophene and polyethylene oxide, or a combination of at least one of the polypyrrole, polyaniline, polythiophene and polyethylene oxide and at least one of the copolymers; Preferably, in the first coating layer, the mass ratio of the sulfur-doped graphene to the auxiliary agent is 1:(3-7).

4. The sodium ion battery phosphate positive electrode material according to any one of claims 1 to 3, characterized in that: Based on the total mass of the sodium ion battery phosphate positive electrode material as 100%, the mass fraction of the second coating layer is 0.5-20%; Preferably, in the second coating layer, the mass fraction of nitrogen in the nitrogen and phosphorus co-doped carbon material is 0.01-0.8%; Preferably, in the second coating layer, the mass fraction of phosphorus element in the nitrogen and phosphorus co-doped carbon material is 0.01-1%.

5. The sodium ion battery phosphate positive electrode material according to any one of claims 1 to 4, characterized in that: The sodium ion battery phosphate positive electrode material also includes a nitrogen-doped oxygen-containing compound, and the nitrogen-doped oxygen-containing compound performs ion doping on the sodium ion battery phosphate positive electrode material; Preferably, the mass fraction of nitrogen in the nitrogen-doped oxygen-containing compound is 0.01-0.8%; Preferably, based on the total mass of the sodium ion battery phosphate positive electrode material being 100%, the mass fraction of the nitrogen-doped oxygen-containing compound is 0.1-5%; Preferably, the oxygen-containing compound in the nitrogen-doped oxygen-containing compound includes doped boron phosphate, and the doped boron phosphate is boron phosphate doped with sodium and / or potassium; Preferably, the chemical formula of the sodium and / or potassium doped boron phosphate is Na m K n B 1-x / 3 PO4, where m+n=x, 0.01≤x<0.15; Preferably, the nitrogen-doped oxygen-containing compound further comprises at least one of zinc oxide, copper oxide, cuprous oxide, magnesium oxide, vanadium oxide and metatitanic acid; Preferably, the oxygen-containing compound in the nitrogen-doped oxygen-containing compound includes a composition of at least one of zinc oxide, copper oxide, cuprous oxide, magnesium oxide, vanadium oxide and titanic acid and the boron phosphate doped with sodium and / or potassium, and the mass proportion of the boron phosphate doped with sodium and / or potassium in the composition is more than 50%.

6. A method for preparing a sodium ion battery phosphate positive electrode material according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: (1) mixing a first carbon source, a metal source, a phosphorus source, oxalic acid and a template to obtain a mixture; (2) After calcining the mixture described in step (1), the template is removed to obtain a mesoporous phosphate precursor coated with the first carbon source in situ; (3) mixing the mesoporous phosphate precursor in situ coated with the first carbon source described in step (2) with a sodium source and a second carbon source, sand-milling, spray drying, and calcining to obtain the sodium ion battery phosphate positive electrode material; Wherein, the first carbon source includes sulfur-doped graphene, and the second carbon source includes nitrogen and phosphorus co-doped carbon material.

7. The method for preparing the sodium ion battery phosphate positive electrode material according to claim 6, characterized in that: Step (1) The first carbon source also includes a conductive polymer; Preferably, the metal source in step (1) is a vanadium source, and the prepared phosphate cathode material is a sodium vanadium phosphate cathode material; Preferably, the vanadium source includes at least one of V2O5, V2O3, NH4VO3 or VOC2O4; Preferably, the phosphorus source in step (1) comprises at least one of sodium phosphate, potassium phosphate, triammonium phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, sodium dihydrogen phosphate, dipotassium hydrogen phosphate, potassium dihydrogen phosphate, disodium hydrogen phosphate, iron phosphate, manganese phosphate, lithium phosphate, lithium dihydrogen phosphate or phosphoric acid; Preferably, the template in step (1) comprises at least one of SBA-15, KIT-6 or mesoporous carbon; Preferably, in step (1), the molar ratio of the metal source, oxalic acid and template is 1:(2-8):(0.1-12); Preferably, after the mixing in step (1), ultrasonic treatment and drying are performed to obtain a dry mixture; Preferably, the temperature of the ultrasonic treatment is 25-100°C; Preferably, the power of the ultrasonic treatment is 30-200W; Preferably, the ultrasonic treatment time is 1-10 h.

8. The method for preparing the sodium ion battery phosphate positive electrode material according to claim 6 or 7, characterized in that: The calcination in step (2) is carried out in a protective atmosphere, wherein the gas in the protective atmosphere comprises at least one of argon, helium or nitrogen; Preferably, the calcination temperature in step (2) is 150-650°C; Preferably, the calcination time in step (2) is 1-30h; Preferably, the method for removing the template in step (2) is: using an alkaline solution to perform an alkali dissolution treatment on the calcined product to remove the template; Preferably, the alkali in the alkaline solution comprises sodium hydroxide and / or potassium hydroxide; Preferably, the temperature of the alkali dissolution treatment is 25-120°C; Preferably, the alkaline dissolution treatment is followed by washing and drying steps, and the detergent used for washing is water.

9. The method for preparing the sodium ion battery phosphate positive electrode material according to any one of claims 6 to 8, characterized in that: The sodium source in step (3) comprises at least one of sodium chloride, sodium bromide, sodium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium sulfate, sodium carbonate, sodium hydroxide, sodium acetate, sodium nitrate, sodium oxalate, sodium formate, sodium tert-butoxide, sodium benzoate or sodium citrate; Preferably, the vanadium source, phosphorus source and sodium source are added according to the ratio of each element in the chemical formula Na3V2(PO4)3; Preferably, the second carbon source in step (3) further comprises a nitrogen-doped oxygen-containing compound; Preferably, the particle size D50 of the material after sand grinding in step (3) is 250-650nm; Preferably, the sand milling in step (3) is carried out in a solvent, and the solvent includes at least one of water, isopropanol, ethylene glycol, acetone, tetrahydrofuran, ether, benzene, toluene or dimethylformamide; Preferably, the spray drying temperature in step (3) is 25-220°C; Preferably, the calcination in step (3) is carried out in a protective atmosphere, and the gas in the protective atmosphere comprises at least one of argon, helium or nitrogen; Preferably, the calcination temperature in step (3) is 500-1050°C; Preferably, the calcination time in step (3) is 1-24h; Preferably, after the calcination in step (3) is completed, cooling and crushing and classification steps are performed.

10. A sodium ion battery, characterized in that: The sodium ion battery comprises the sodium ion battery phosphate positive electrode material according to any one of claims 1 to 5.